The safety and efficacy of Houtou Jianweiling tablet in patients with chronic non-atrophic gastritis: a double-blind, non-inferiority, randomized controlled trial - Shah, Muhammad Raza; Fatima, Samreen; Khan, Sehrosh Naz; Shafiullah,; Azam, Zahid; Shaikh, Hafeezullah; Majid, Shahid; Chengdong, He; Daijun, Zhou; Wang, Wei (Frontiers in Pharmacology, 2024)
The Houtou Jianweling Tablet (HTJWT) is a Chinese patent medicine that has been clinically utilized for over two decades, demonstrating efficacy in treating Chronic Non-atrophic Gastritis (CNAG) symptoms. This study, a phase II double-blind randomized trial, aimed to evaluate the clinical efficacy and safety of HTJWT in Pakistani patients with mild to moderate CNAG symptoms. A total of 240 patients were randomly assigned to either the control group (Omeprazole) or the treatment group (HTJWT) in a 1:1 ratio. The primary efficacy indicators included improvement rates of gastric distention and gastralgia. Secondary indicators encompassed various clinical symptoms and signs, such as visual analogue score, H. pylori conversion rate, and safety assessments. Both groups exhibited good drug compliance, and baseline characteristics were comparable. The clinical improvement rate was similar between the treatment and control groups (91.1% vs. 91.0%), with no significant difference. The negative conversion rate of H. pylori also showed negligible variation. Safety indicators and adverse events were comparable, indicating that HTJWT was well-tolerated. The lower limit of confidence interval (CI, 95%) for the differences in the effective rate between the treatment and the control groups was found to be -0.0781 which is greater than -0.15, hence the treatment group is non-inferior to the control group. The therapeutic dosage used in the trial and treatment period did not cause any significant adverse event, and there were no obvious changes in the ECG profile, vital signs and biochemistry of the patients. Based on the clinical efficacy evaluation and reported adverse events, it can be concluded that the HTJWT is a safe and effective traditional Chinese medicine for the treatment of patients suffering from chronic non-atrophic gastritis with mild to moderate symptoms.